QR code payment in Indonesia and its application on mobile banking - Ruslan, .; Karmawan, Gusti Made; Suharjito, .; Fernando, Yudi; Gui, Anderes (KnE Social Sciences, 2019)
The technology innovation makes it easy for us to connect to various services. Banking transactions that previously could only be served only at Branch Offices, ATMs (Automatic Teller Machines) and EDC (Electronic Data Capture), now they can be accessed online. Balance information, fund transfers, credit purchases, PLN tokens, payment of PAM and BPJS bills, all can be done through Mobile Banking application from smartphones. This study aims to find out how QR Code on Mobile Banking provides convenience in making payment transactions and how it can be used safely. The research was conducted through literature study, observation, and distribution of questionnaires to 30 respondents to identify the system acceptance. Payment Model QR Code on Mobile Banking can be widely used as an alternative of cash payment through a smartphone. The developed system does not only for merchant payment but can be used for person to person payment. The result of this research is a prototype for QR Code Payment on OCBC NISP Mobile Banking which can be used as an alternative payment system and integrated with fund source account without the need to top up the transfer.